Metode Ilhaqy Ala Kiai Kampung terhadap Hukum Tembakau di Desa Tlogorejo Kecamatan Karangawen Kabupaten Demak Jawa Tengah - Ahmad Munif (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Religious leaders or Muslim clerics in rural village (Kiai Kampung) unquestionably become role models, especially, in relation to their views on Islamic law. The problems of Islamic law in community cover various matters of people’s life, and one of which is tobacco. This research aimed at revealing the village kiais’ views and how the Ilhaqy method they used in explaining the ruling of tobacco that allows tobacco cultivation and transactions though tobacco is the basic ingredient of making cigarettes. The study design relied on a qualitative approach in which the reseacher goes “into the field” to observe the phenomemon in its natural seeting. Data were obtained through in-depth interviews and observations. By elaborating ushuliyah and sociological approach, the results of this study suggested that, first, the kiai of Tlogorejo village argued that the ruling of making tobacco as an object of buying and selling is permissible (mubah) even though there are other opinions that the smoking is prohibited (haram). Second, the approaches used by Kiai Kampung in Tlogorejo in issuing legal opinion on tobacco range from qawliy (opinion-based) and ilhaqiy (finding the equivalent of a similar case in classical Islamic law). Qawliy means following the previous views of Muslim clerics while ilhaqiy finding the similarity between the harmless things that are permissible and tobacco which is not harmful.